(untitled) (PJDOL, 2023)
In Pakistan, Allama Iqbal Open University (AIOU) and some other conventional universities are imparting higher education through distance learning system. These higher education institutions try to modernize their teaching process with the new trends and practices going on around the world to equip their students with latest content knowledge and research methodologies. Allama Iqbal Open University is Pakistan’s pioneer university which laid the foundation of distance learning system for the first time when this concept was not much popular around the world, but AIOU has proven its worth and now its services are acknowledged all over the country. L